Effects of contrasting colour patterns of the ball in the volleyball reception - Lenoir, M.; Vansteenkiste, J.; Vermeulen, J.; de Clercq, D. (Journal of Sports Sciences, 2005)
The effects of three different colour patterns on the surface of volleyballs (versus that of a plain white ball) on the behaviour of a reception player were examined by presenting sidespin volleyball serves. Expert (n=10) and novice (n=10) volleyball players intercepted volleyballs projected straight at them or at an initial angle of 9.5° outwards but eventually curving towards the players' original position. In the latter trajectories, players generally took one or more steps laterally before returning to the landing position of the ball. These excursion patterns were significantly more pronounced with the white balls than the coloured balls. Differences between balls of different colour combinations were also observed. The first finding supports the thesis that next to a prospective type of control, such as on-line maintenance of a certain spatiotemporal relationship between the player and the ball, properties of the ball itself allow prediction of the future path of the ball. Differences between types of colour patterns are explained within the framework of the between-colours wavelength contrasts of each type of ball.